Analisis Pengaruh Elemen Subjective Well-Being terhadap Organizational Citizenship Behavior Karyawan - Rezqi Ananda Basid; Alya Risma Elfariani (Fakultas Ekonomi Universitas Islam 45, 2020)
This study examined the relationship between subjective well-being (SWB) and its aspects such as life satisfaction, positive affectivity and negative affectivity to organizational citizenship behavior (OCB) in employee of PT Sorak Gemilang Persada. Participants in this study were 54 employees of PT Sorak Gemilang Persada. Measuring instruments used was a modified questionnaire of Satisfaction with Life Scale and Positive and Negative Affectivity Schedule, both instruments used to measure SWB. Meanwhile, OCB were measured by the Organizational Citizenship Behavior Scale. The data obtained were analyzed by simultaneous and partial test with SPSS for Windows ver. 26. The results indicate that there was a positive correlation between life satisfaction and positive affectivity to OCB. Meanwhile, there was a negative correlation between negative affectivity and OCB of PT Sorak Gemilang Persada’s employees. Both three of these variables gave an effective contribution as much as 40% while the rest came from other factors.